Exercise response on dose curve among class I obese young adult population - Hassan, Batool; Farooqui, Sumaira Imran; Farhad, Ali (Journal of the Pakistan Medical Association, 2022)
Objective: To identify exercise regimes having a short duration and yet incorporating the effects of both aerobic and resistance exercises. Method: The randomised study was conducted from December 1, 2019, to April 31, 2020, at Ziauddin Hospital, Karachi, and comprised individuals of either gender aged 20-40 years with class-I obesity. All participants were initially screened using a physical activity and readiness questionnaire to determine if they were fit to perform the exercises. Subsequently, dynamic exercises were introduced based on the guidelines of the American College of Sports Medicine. The subjects were randomised into aerobic group A, resistance group B and dynamic resistance group C. The intervention lasted 12 weeks. The quantification of exercises was done using the frequency, intensity, time, and type protocol. Results: The results were analysed on MedCalc statistical software. Out of the 102 participants, 51(50%) each were males and females. Each of the three groups had 34(33.3%) subjects; 17(50%) males and as many females. The impact was significant in all the three groups (p<0.05). The effect was significantly better in group C than groups A and B. Conclusion: Body mass index and body fat percentage values improved through aerobic, resistance and dynamic resistance exercises. Key Words: Exercise, Body fat mass, Obesity, BMI. Continuous...